2019
DOI: 10.1111/ajad.12884
|View full text |Cite
|
Sign up to set email alerts
|

Worries About Discontinuing Buprenorphine Treatment: Scale Development and Clinical Correlates

Abstract: Background and Objectives: Despite the benefits of maintenance buprenorphine treatment for opioid use disorder (OUD), many individuals report an interest in discontinuing the medication, while also expressing worries about tapering. The purpose of this study was to develop a measure of worries about buprenorphine discontinuation ("Off Bupe") and determine the demographic and clinical characteristics associated with these worries. Methods: Between May 2017 and May 2018, we surveyed adults in an outpatient prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…In one study of patients with OUD enrolled in buprenorphine maintenance therapy, 89.9% of the participants reported that concerns about withdrawal were a primary reason for continuing treatment ( 37 ). In addition, the degree of concern about stopping buprenorphine maintenance was positively correlated with self-reported desire to avoid physical discomfort ( 35 ). Therefore, in human patients with OUD, fear of anticipated withdrawal symptoms and the desire to escape somatic and emotional discomfort are major motivational factors that drive continued opioid use.…”
Section: Cues Associated With Negative Reinforcement Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study of patients with OUD enrolled in buprenorphine maintenance therapy, 89.9% of the participants reported that concerns about withdrawal were a primary reason for continuing treatment ( 37 ). In addition, the degree of concern about stopping buprenorphine maintenance was positively correlated with self-reported desire to avoid physical discomfort ( 35 ). Therefore, in human patients with OUD, fear of anticipated withdrawal symptoms and the desire to escape somatic and emotional discomfort are major motivational factors that drive continued opioid use.…”
Section: Cues Associated With Negative Reinforcement Learningmentioning
confidence: 99%
“…Several studies have reported in human patients with OUD that avoiding the onset of withdrawal symptoms is a major motivation for continuing opioid use (i.e., conditioned negative reinforcement) (2,33). For patients with OUD undergoing opioid substitution treatment with buprenorphine or methadone, withdrawal discomfort and greater pain were major concerns when choosing to taper off treatment (34)(35)(36). In one study of patients with OUD enrolled in buprenorphine maintenance therapy, 89.9% of the participants reported that concerns about withdrawal were a primary reason for continuing treatment (37).…”
Section: Conditioned Negative Reinforcementmentioning
confidence: 99%
“…Most saliently, although the risk is diminished as compared to full opioid agonists, buprenorphine still carries with it the class-wide risk for fatal respiratory depression upon overdose, alone and in combination with other CNS depressants . Furthermore, the optimal approach for treatment of acute pain in the context of chronic buprenorphine therapy for OUD remains an area of active concern and debate. , Similarly, patients, providers, and payers have widely divergent opinions on the desirability of lifetime treatment with buprenorphine, highlighting ongoing tensions regarding indefinite use of MAT for OUD. …”
Section: History and Importance In Neurosciencementioning
confidence: 99%
“…Zudem angeregt werden könnte, die BSCL (oder vergleichbare Instrumente) routinemäßig in (teil-) stationären Settings dafür einzusetzen. Dabei sollten tatsächlich vorhandene symptomatische Beschwerden von möglichen Sorgen über gegebenenfalls auftretende Symptome differenziert werden [35].…”
Section: Merkeunclassified